Efficacy of anesthetic agents to delay pain onset after periodontal surgery. - Steffens, Joao Paulo; Pochapski, Márcia Thaís; Santos, Fábio André; Pilatti, Gibson Luiz (American Dental Society of Anesthesiology (ADSA), 2011)
The aim of this study was to evaluate the influence of 2 anesthetic agents on patients' postoperative pain perception after periodontal surgery. For this parallel-group, double-blinded, randomized clinical trial, 36 open flap debridement surgeries were performed on patients who presented with periodontal disease with clinical signs of inflammation after nonsurgical treatment on at least 1 quadrant. Patients were allocated to 1 of the following groups: group 1, 2% lidocaine with 1100,000 epinephrine; group 2, 2% mepivacaine with 1100,000 norepinephrine. Pain intensity was assessed using the visual analog scale during the first 8 hours after surgery. All patients received 750-mg acetaminophen tablets, which they were instructed to take as a rescue medication if necessary. The results demonstrated that postoperative pain intensity was statistically lower in group 2 than in group 1 at the 1-, 2-, and 3-hour periods after surgery, although the pain intensity for all groups could be considered mild. In conclusion, patients in both groups reported similar mild pain after periodontal surgery.